Enhancing the inhibition of dental erosion and abrasion with quercetin-encapsulated hollow mesoporous silica nanocomposites - Chen, Jia-Min; Cheng, Yi-Ling; Yang, Meng-Hui; Su, Chen; Yu, Hao (Frontiers in Bioengineering and Biotechnology, 2024)
Dental erosion and abrasion pose significant clinical challenges, often leading to exposed dentinal tubules and dentine demineralization. The aim of this study was to analyse the efficacy of quercetinencapsulated hollow mesoporous silica nanocomposites (Q@HMSNs) on the prevention of dentine erosion and abrasion. Q@HMSNs were synthesized, characterized, and evaluated for their biocompatibility. A total of 130 dentine specimens (2 mm × 2 mm × 2 mm) were prepared and randomly distributed into 5 treatment groups (n = 26): DW (deionized water, negative control), NaF (12.3 mg/mL sodium fluoride, positive control), Q (300 μg/mL quercetin), HMSN (5.0 mg/mL HMSNs), and Q@HMSN (5.0 mg/mL Q@HMSNs). All groups were submitted to in vitro erosive (4 cycles/d) and abrasive (2 cycles/d) challenges for 7 d. The specimens in the DW, NaF, and Q groups were immersed in the respective solutions for 2 min, while treatment was performed for 30 s in the HMSN and Q@HMSN groups. Subsequently, the specimens were subjected to additional daily erosion/abrasion cycles for another 7 d. The effects of the materials on dentinal tubule occlusion and dentine organic matrix (DOM) preservation were examined by scanning electron microscopy (SEM).The penetration depth of rhodamine B fluorescein into the etched dentine was assessed using confocal laser scanning microscopy (CLSM). The erosive dentine loss (EDL) and release of type I collagen telopeptide (ICTP) were measured. The data were analysed by one-way analysis of variance (ANOVA) with post hoc Tukey's test (α=0.05). Q@HMSNs were successfully synthesized and showed minimal toxicity to human dental pulp stem cells (HDPSCs) and gingival fibroblasts (HGFs). Q@HMSNs effectively occluded the dentinal tubules, resulting in a thicker DOM in the Q@HMSN group. The CLSM images showed more superficial penetration in the HMSN and Q@HMSN groups than in the quercetin, NaF, and DW groups. The Q@HMSN group exhibited a significantly lower EDL and reduced ICTP levels compared to the other groups (p < 0.05). In conclusion, Q@HMSNs hold promise for inhibiting dentine erosion and abrasion by promoting tubule occlusion and DOM preservation.